Youth-friendly services was the magic: Experiences of adolescent girls and young women in the community PrEP study, South Africa - Emily Krogstad Mudzingwa; Lindsey de Vos; Lauren Fynn; Millicent Atujuna; Ingrid T. Katz; Sybil Hosek; Connie Celum; Joseph Daniels; Linda-Gail Bekker; Andrew Medina-Marino (Taylor & Francis Group, 2024)
ABSTRACTAdherence to daily oral pre-exposure prophylaxis (PrEP) for HIV prevention has been challenging for adolescent girls and young women (AGYW). As part of The Community PrEP Study (CPS), AGYW were randomised to HIV-prevention empowerment counselling (intervention) or basic medication pick-up (control). In this qualitative sub-study, we interviewed AGYW participants (n = 39) to explore PrEP use and study experiences by study arm, and study staff (n = 7) to explore study implementation, site environment, and participant engagement. Data were thematically analysed using a constant comparison approach. Comparative matrices assessed similarities and differences in study experiences and PrEP support preferences. Friendly, non-judgmental, non-stigmatizing study staff were described as central to participant's positive experiences. Participants highly valued CPS staff's holistic health support (e.g. physical and psycho-social). Intervention participants described empowerment counselling as helpful in supporting PrEP disclosure. However, control participants also described disclosing PrEP use to trusted individuals. Participants and staff recommended public-sector PrEP services provide holistic, confidential, and integrated sexual and reproductive health services, and community sensitisation. An adolescent and youth-friendly environment was the primary factor motivating AGYW's study engagement. While HIV-prevention empowerment counselling was well received, welcoming, respectful and non-judgmental staff may be the 'secret sauce' for implementing effective PrEP services to AGYW.